2017
DOI: 10.4274/jcrpe.3790
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Parental Weight Status in Children and Adolescents

Abstract: Objective:This study aims to assess the relationship between body mass index (BMI) of children and that of their parents in a nationally-representative sample of Iranian population.Methods:This cross-sectional nationwide study was conducted in 2011-2012 among 6-18-year-old students and their parents living in 30 provinces of Iran. Socio-demographic information was collected. The BMI values of the children/adolescents were categorized according to the World Health Organization reference curves. Association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 33 publications
8
55
0
16
Order By: Relevance
“…A study involving children and parents from Iran confirms that parental obesity is a factor in childhood and adolescent obesity. Therefore, it is important to prevent obesity in children who have one or more obese parents [36].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving children and parents from Iran confirms that parental obesity is a factor in childhood and adolescent obesity. Therefore, it is important to prevent obesity in children who have one or more obese parents [36].…”
Section: Discussionmentioning
confidence: 99%
“…The association of obesity in adolescents with maternal, but not paternal, BMI was a peculiar finding of the present study, because in the majority of other works, obesity was associated with overweight in both parents. (9,10) It can be suggested that the identified association is realized via the primary role of a mother in the formation of family ambience in rural communities, which, in its turn, determines the eating patterns and lifestyle of a child.…”
Section: Discussionmentioning
confidence: 99%
“…Наше исследование подтвердило известный факт сопряженности ожирения в детском и подростковом возрасте с семейной отягощенностью по данному заболеванию [7,[9][10]. Наличие такой связи сложно опосредуется взаимодействием генетических факторов с факторами семейного окружения, формирующими так называемое обесогенное поведение ребенка: низкая физическая активность, длительное экранное время, нездоровые паттерны питания, короткая продолжительность сна.…”
Section: обсуждение основного результата исследованияunclassified
“…Наличие такой связи сложно опосредуется взаимодействием генетических факторов с факторами семейного окружения, формирующими так называемое обесогенное поведение ребенка: низкая физическая активность, длительное экранное время, нездоровые паттерны питания, короткая продолжительность сна. Как интересную находку нашего исследования следует отметить то, что мы, в отличие от большинства других исследователей, показавших связь избыточного веса детей с весом обоих родителей [10,11], обнаружили, что ожирение у сельских подростков связано с ИМТ их матерей, но не отцов. Результаты, сходные с полученными нами, были получены еще в двух исследованиях, в которых, к сожалению, не приведены данные о территории проживания включенных в выборку детей [7,9].…”
Section: обсуждение основного результата исследованияunclassified